PENGARUH BODY IMAGE TERHADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN PONTIANAK - Devi, Rasaz Anisa; Achmadi, Achmadi; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research was to know the effect of body image on the students consumptive behavior to the student of Economic Program in FKIP of Untan Pontianak. The research method used is quantitative descriptive method. This is a correlation research. The sample of research is 32 students of PPAPK Economic Program in FKIP of Untan Pontianak class year of 2013-2016 that work. Data collection tools used are questionnaire and literature or documents. The result of this research showed that the body image to the student of Economic Program in FKIP of Untan Pontianak has a percentage of 66.79% and is categorized into either category. While the consumptive behavior to the student of Economic Program in FKIP of Untan Pontianak has a percentage of 59.58% and classified into the category of being. And there is an effect of body image on the students consumptive behavior to the student of Economic Program in FKIP of Untan Pontianak. It is based on t count > t table (2.891 > 2.042) and significance value 0.007 < 0.05, so Ha is accepted.Keyword :Body Image, Consumptive Behavior, Students.